Is it True That My Students don't Understand the Static Fluid Concepts? Rasch Modeling Perspective - Moh. Irma Sukarelawan; Sriyanto; Miftakhatun Sa’adah; Jimmy Jupri; Fitri Nur Hikmah; Eko Nursulistiyo (Jurnal Pendidikan dan Pengajaran, 2024)
Students' conceptual understanding can be analysed using the Classical Test Theory (CTT) and Item Response Theory (IRT) approaches. CTT can only explain students' conceptual understanding at the group level, while IRT can at the individual level. Therefore, this research evaluates students' conceptual understanding using the Rasch model. This research used a survey research type and was carried out in class XI. Students' conceptual understanding was collected using 10 multiple-choice questions on static fluid material. The level of concept understanding was analyzed in stages using Rasch modelling. Understanding analysis begins by analyzing the difficulty level of the questions and then continues with descriptive analysis. The Wright map is used to see the hierarchy between students' understanding of concepts and the difficulty level of the questions used. Finally, a person diagnostic map will be used to see students' understanding of concepts in detail. The analysis results show that students' conceptual understanding is generally in the high and medium categories. Person diagnostic maps have identified patterns of correct and incorrect answers from students that do not reflect their true abilities. So, it is necessary to analyze the exact location of the weaknesses and strengths of students' conceptual understanding. This has implications for the suitability of the learning plan that the teacher will use.